Characterization of NITI shape memory alloy sintered at different temperatures in reducing environment - Mohd Zaki, Hafizah Hanim; Mohd Sobri, Nur Azemuzahir; Abdullah, Jamaluddin; Sarifuddin, Norshahida; Mohd Daud, Farah Diana (Trans Tech Publications Ltd, 2020)
NiTi has received significant interest as medical implant materials due to its shape memory effect behavior apart from its good biocompatibility and mechanical properties. The formidable challenge of obtaining single phase NiTi from elemental powders via solid state is due to oxidation problem of elemental powders and the oxygen atoms dissolve in NiTi matrix as interstitial impurities forming stable oxygen-rich TiNiOx. This may deterioriate the shape memory behavior of NiTi. This research investigates the use of MgH2 in combination with CaH2 as in-situ reducing agent to eliminate oxidation of the specimen during sintering both at lower and higher sintering temperatures. Here, the effect of sintering temperature on phase formation and transformation behavior of NiTi in reducing environment was studied. The phase formation was characterized by using x-ray diffraction (XRD) where the morphology and elemental analysis were characterized by using the scanning electron microscope (SEM) equipped with EDS. The martensitic transformation behavior was analyzed using differential scanning calorimeter (DSC). The use of MgH2 and CaH2 as reducing agent has a significant influence on the phase formation of NiTi synthesized via solid state especially at 930 °C, where almost single phase NiTi was formed with good transformation behavior. This reducing agent creates a conducive environment for the production of single phase NiTi.